PENDIDIKAN AKHLAK SEBAGAI PONDASI MEWUJUDKAN GENERASI BERKARAKTER - Qodir Akhwandi, Abdul (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2017)
In realizing characterized genaration, moral education becomes very important. This is because any intelligent person, regardless of his position, if not balanced with faith and devotion will only lead people to something contrary to the teachings of the Qur'an and hadith. Moral education is a means that gives man concrete rules or instructions on how he should live and act in a good human life, and how to avoid disgraceful behaviors. Implementation of moral education and noble character for the child, can run well if managed well, through the appropriate education system and can meet the guidance of society.Key Words: moral education, character